The effect of life-threatening traumatic experiences on the personality development of Ukrainians - DANYLIUK, Ivan; BOHUCHAROVA, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. Theoretical and empirical data confirm that war-trauma’ situations associated with parameters of post-traumatic stress disorder (PTSD) and adjustment disorders (AD) negatively affect personality development The purpose of the study is to present evidence of the psychological mechanisms of the effect of war-trauma on the personality development of Ukrainians during the war. Methods. Mississippi scale, Keane et al.; Inventory - Schmieschek, Adaptability, Agaev et al., Values-in-action, Seligman et al.; Big Five Locator, Howard et al. Results. As to the MS, the sample was divided into two polar groups of Ukrainians. One - 128 (56,9 %) participants after the war-trauma’ exposure, remain adjusted, which indicates the evolutionary resourcefulness of their personality development. Another - 97 (43.1 %) has signs of unadjusted - AD and PTSD - due to a life-threatening traumatic experience (36,9 % vs. 6,2 %). The Adaptability-data confirmed statistically significant differences (by t-test) between thеsе polar groups, especially in such components as neuropsychological stability and moral normativity (t = 7,945, & t = 8,743, p = 0,000). Significantly more often in the pre-traumatic period, there are differences in character accentuations as potential RA / PTSD risk factors in the two groups (t-test): anxious, excitable, emotional, dysthymic, cyclothymic, stuckic. In the post-trauma, there are other differences in the tendencies to increase accentuations in: dysthymic, stuckic, anxious, excitable, demonstrative, pedantic types. Correlation analysis confirmed that the "top-five" personality traits (Big Five) ак reliable predictors for positive sociocultural personality development in well-adjusted individuals. In the polar group, v. v the "bottom-five" traits - neuroticism, social maladjustment, high emotionality, depression, deviations in behavior are predictors of traumatic personality development. It was established: the higher the level of adjustment disorders, the lower the level of manifestation of such positive values as "wisdom", "courage", "justice", but there is a positive relationship between PTSD / AD indicators and the values "mildness" and "transcendence" (by F-Fisher, all p = 0,000 level). Conclusions. The PTSD, personality-related problems of Ukrainians in the post-trauma period are easier to overcome, the shorter the exposure to the severe war-trauma and the sooner the life-threatening traumatic experience is identified by psychologists.